Types of Painting and Art in the City of Kfrî (A Field Study) Selected Example - Barznji, Dr. Mahdi Calal Mustafa (Sulaimani Journal for Humanities, 2025)
This research is about the different types of painting and the different materials used, here we focus on painting on wood, stone and plaster, these three types of materials are one of the raw materials of Islamic art Therefore, we consider it important to talk about the art of painting in this ancient city, which still has many archaeological remains. We tried to choose some examples of each material, such as the palace of Majid Pasha Baban, which dates back to the early nineteenth century Most of them are painted on plaster, with botanical, geometric, animal, human, bird, authoritarian and religious symbols. Second type: Sardar and board patterns, the history of these materials goes back to the late nineteenth and early twentieth centuries, such as the window patterns of Majid Pasha's house and patterns and pictures on boxes and buffets and vases with bright colors. Type 3: Stone is another material that is carved with patterns and paintings. Stone is one of the basic building materials of Kufri region such as marble and stone Khanaqah Kufri and House of Sayed Mohsen Zor etc. This research focuses on the types of patterns and paintings, the method of painting and analysis of the genres and compares them with patterns and paintings of other regions of Kurdistan, Mosul and Samarra.
Keywords: Patterns and paintings; materials of architectural